An Evaluation of VRSA Isolates from Hospitalized Patient’s in Karachi - Shamsul Arfin Qasmi, Aftab Ahmed Khan, Adnan Kanpurawala, Anwar All Akhund, Rabiyah Pirzada, Hasan Askari (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: The aim of this study is to determine vancomycin resistance or susceptibility in patients visiting different hospitals in Karachi, Pakistan. Place and Duration of study: Med Path Laboratories and Diagnostic Center, Gulshan-e-Iqbal Karachi & KESC Medical center. Karachi during Jan, 2013 to may, 2013. Material and Methods: The present study deals with the distribution 100 isolates from various hospitals located in Karachi and studied by Kirby Bauer disk diffusion procedure at Med Path Laborites and Diagnostic Center KESC Medical Center. Results: The study shows out of 100 isolates 20% were resistant, 2% were intermediate and 78% were sensitive. Conclusion: Now there is an immediate need to slow down the spread of these strains (VRSANISANSSA) as much as possible with safety precautions and good infection control methods. The number ofpersons caring for the patient should be minimized and dedicated staff should be assigned to treat the VISANRSA patient. Implementation of the appropriate infection control precautions during patient care must be monitored.